Occurrence of pattern formation of microstructural, physical and mechanical properties of sintered PM steels containing pre-alloyed Astaloy E powder - Ostovan, Farhad; Matori, Khamirul Amin; Mohamed Yusoff, Hamdan; Yunus, Robiah; Mohamed Ariff, Azmah Hanim; Toozandehjani, Meysam; Fadaeifard, Firouz; Meschian, Mohammad Reza (Springer, 2014)
The occurrence of pattern formation within physical dimension and mechanical property changes was systematically investigated based on the addition of various amounts of pre-alloyed Astaloy E and carbon to iron powder. Powder samples were prepared in a similar manner by mixing in a Y-type mixer, compacting in a floating die under constant pressure and sintering in a hydrogen atmosphere tunnel furnace at 1,120 °C for 45 min. An optical microscope equipped with image analysis was employed to study the microstructure. Physical properties, such as the green density, sintered density and dimensional changes, as well as the hardness were measured. The results indicate that the addition of Astaloy E and carbon results in increased green density, sintered density and hardness. An increase in the carbon content resulted in physical dimension growth of the parts.